Spontaneous preterm delivery is reflected in both early neonatal and maternal gut microbiota - Hiltunen Henni; Carmen Collado Maria; Ollila Helena; Kolari Terhi; Tölkkö Satu; Isolauri Erika; Salminen Seppo; Rautava Samuli (SPRINGERNATURE, 2022)
Abstract
Background
Aberrant gut microbiota composition in preterm neonates is linked to adverse health consequences. Little is known about the impact of perinatal factors or maternal gut microbiota on initial preterm gut colonization.
Methods
Fecal samples were collected from 55 preterm neonates (<35 gestational weeks), 51 mothers, and 25 full-term neonates during the first 3–4 postpartum days. Gut microbiota composition was assessed using 16S ribosomal RNA gene sequencing.
Results
Preterm neonates exhibited significantly lower gut microbiota alpha diversity and distinct beta diversity clustering compared to term neonates. Spontaneous preterm birth was associated with distinct initial gut microbiota beta diversity as compared to iatrogenic delivery. Gestational age or delivery mode had no impact on the preterm gut microbiota composition. The cause of preterm delivery was also reflected in the maternal gut microbiota composition. The contribution of maternal gut microbiota to initial preterm gut colonization was more pronounced after spontaneous delivery than iatrogenic delivery and not dependent on delivery mode.
Conclusions
The initial preterm gut microbiota is distinct from term microbiota. Spontaneous preterm birth is reflected in the early neonatal and maternal gut microbiota. Transmission of gut microbes from mother to neonate is determined by spontaneous preterm delivery, but not by mode of birth.
Impact
The initial gut microbiota in preterm neonates is distinct from those born full term. Spontaneous preterm birth is associated with changes in the gut microbiota composition of both preterm neonates and their mothers. The contribution of the maternal gut microbiota to initial neonatal gut colonization was more pronounced after spontaneous preterm delivery as compared to iatrogenic preterm delivery and not dependent on delivery mode.
Our study provides new evidence regarding the early gut colonization patterns in preterm infants.
Altered preterm gut microbiota has been linked to adverse health consequences and may provide a target for early intervention.